Scanning probe-based in situ high temperature electrical and electrochemical measurements in atmospheric pressure - Ng, Chee Seng (2019)
Atomic force microscopy (AFM)-based study of electrical and electrochemical properties of a material/system at an elevated temperature in atmospheric pressure has been limited to ~250°C in conventional AFM setups. In this report, we have demonstrated the viability of a new approach for high temperature electrical and electrochemical studies (up to 700°C) in a conventional AFM setup by employing a combination of a micron-scale heater stage (MHS) and custom-made all-metal tips. We present the design, fabrication process and characterization of the MHS and all-metal tips. A temperature dependent impedance measurement on an MHS-integrated half-cell was then successfully demonstrated with a custom-made Pt-Ir tip. Issues and possible room to improve regarding the new approach are also discussed.